THE EFFECT OF PRINCIPAL LEADERSHIP, COMPENSATION, ENVIRONMENT, AND MOTIVATION ON TEACHER PERFORMANCE - Atok Suyoto; Kartika Hendra TS; Sudarwati Sudarwati (STIE PENA, 2025)
This study aims to determine and explain the influence of principal leadership, compensation, work environment, and motivation on teacher performance at the Bina Insan Muda Boyolali Foundation. The study population was 46 teachers at the Bina Insan Muda Boyolali Foundation, using a saturated sample. Data collection used a questionnaire. Data analysis used Multiple Linear Analysis. The results showed that principal leadership, work environment, work motivation, and compensation had a positive and significant influence, contributing 85.9% to teacher performance, while the remaining 14.1% was explained by other variables not included in this study. This study suggests that teachers at the Bina Insan Muda Boyolali Foundation can improve their work motivation in a conducive environment under the leadership of a principal who pays attention to the compensation received by teachers to improve school performance. Keywords: Performance, Principal Leadership, Compensation, Work Environment, Work Motivation, Teachers